Gojek online transportation consumer loyalty is seen from the quality of service and brand image - Prasetya, Hendra; Azizah, Nurul (Institute of Computer Science (IOCS), 2024)
To find out the direction and significance of the partial influence of service quality and brand image on consumer loyalty of users of Gojek online transportation services among students of the Faculty of Economics and Business, Wijaya Kusuma University Surabaya is the aim of this research. The population used as the population were students from the Faculty of Economics and Business, Wijaya Kusuma University, Surabaya, with the sample determined using purposive sampling. The characteristics of the sample are that they have the Gojek application and have placed orders at least 2 (two) times. The sample processed was 100 (one hundred) respondents. Data was collected through distributing questionnaires. Data processing uses multiple linear regression analysis and the hypothesis is tested using the t test or partial test. The result is that service quality and brand image partially have a positive and significant effect on consumer loyalty of Gojek online transportation service users among students at the Faculty of Economics and Business, Wijaya Kusuma University, Surabaya. The quality of service must continue to be improved, among other things, by creating a sense of security for consumers, competent drivers, and standard equipment. Cultivating a positive brand image, among other things, by improving the company's reputation, applications that are easy to operate